Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
This issue of KIU Journal of Social Sciences focuses on Development Administration, Social Psychology, Educational Psychology, Educational Management, Entrepreneurship Studies, Legal Studies, Teaching and Learning Skills, Enterpreneurship and Business Studies, as well as Literary and Media Studies. The first part of the Journal addresses issues in Development Administration such as rural and urban development policies in Nigeria as well as the politics and effects of removal of ptetoleum subsidy. It is argued in one of the papers that there is something fundamentally wrong in government allowing the World Bank and the International Monetary Fund (IMF) agents to run the economy and co-ordinate Ministers. It therefore suggests that increased awareness, public enlightenment, subsidy reinvestment and empowerment programmes are some of the ways forward. Sections two, three, four and five explore the social and cultural factors that affect the academic performance of students in various institutions of learning in the society. One of the papers suggests that students and teachers should be given adequate knowledge of health education in order to create a sustainable quality of live to control pollution, the spread of diseases and to prevent accidents within the school environments. Health education knowledge should also be given to control physical, chemical and biological processes which may directly and indirectly affect the wellbeing of students and teachers in schools. In the Section on Entrepreneurship and Business Studies, it is recommended that entrepreneurship education should encourage and provide more opportunities for the teaching personnel towards capacity building due to their significant effect towards venture creation potential among the graduates. This is drawn from the conclusion that entrepreneurship education teaching personnel has a strong positive relationship with venture creation potentials among graduates of higher institutions. It has also been observed that the media is very important in order to achieve a sustainable development and in the search for an economic development agenda/program that empowers people. Against this backdrop, the papers in part seven amplify that central tenet. Theoretical, methodological and practical implications are discussed in the papers. In particular, the results recommended the need for television programs to increase agribusiness programs in their airing, the television stations increase the coverage use to televise agribusiness, the need for the government to support the television stations in their agribusiness programs, the farmers should be made aware of the intention of the show and how it would be of great benefit to them and other farmers in all the parts of the country. It has been observed that the administration of justice, in all countries and at all times is a subject broad and difficult, both in its operation and its influence. It is perhaps more indicative, a truer test, of the real temper and spirit, both of the government and the people of the state or country, than any other thing. This is why the papers in the last part of this edition focus on Legal Education. On the whole, this issue of KIU Journal of Social Sciences contains papers that have information on all aspects of human life. Collaborative and cooperative approaches are offered as best approaches for dealing with matters that lead to the instability of communities, societies, economies, and the environment. The theoretical analyses provide opportunities to operationalize the theories discussed in the articles. The authors’ teachings and areas of research must have certainly influenced their perspectives on the diagnoses of the matters they have addressed in their articles. Professor Oyetola O. Oniwide College of Humanities and Social Sciences, Kampala International University, P.O. Box 20000, Kampala, Uganda.